2012
DOI: 10.1080/17480272.2012.663407
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on the durability of heat-treated White Birch (Betula papyrifera) subjected to the attack of brown and white rot fungi

Abstract: The effect of heat treatment on decay resistance of white birch was evaluated for different incubation periods ranging from 2 to 12 weeks using three species of brown rot and one species of white rot fungus. The results of weight loss tests showed that the white rot fungus, Trametes versicolor, effectively degraded the untreated wood (73.5%). While the degradation of untreated wood by brown rot fungi species, Gloephyllum trabeum (11.6%) and Conifora puteana (6.2%), was considerably less compared to T. versicol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…Hakkou et al (2006) found a significant correlation between biological durability and the thermal modification temperature. Decay resistance tests conducted by MetsaKortelainen and Viitanen (2009) on the sapwood and heartwood of Scots pine and Norway spruce, which have been thermally modified at 170-230°C using the thermowood method, against soft and brown rot fungi, also confirmed that the increasing thermal modification temperature increases the decay resistance.The improvement of biological durability in different species of thermally modified wood was also reported by Kamdem et al (2002), Jones et al (2006), Calenego et al (2010), and Lekounougou and Kocaefe (2012). According to published data, there are several reasons for the increase in the biological durability of thermally modified wood.…”
Section: Effect Of Thermal Modification Temperature On the Mechanicalsupporting
confidence: 64%
See 2 more Smart Citations
“…Hakkou et al (2006) found a significant correlation between biological durability and the thermal modification temperature. Decay resistance tests conducted by MetsaKortelainen and Viitanen (2009) on the sapwood and heartwood of Scots pine and Norway spruce, which have been thermally modified at 170-230°C using the thermowood method, against soft and brown rot fungi, also confirmed that the increasing thermal modification temperature increases the decay resistance.The improvement of biological durability in different species of thermally modified wood was also reported by Kamdem et al (2002), Jones et al (2006), Calenego et al (2010), and Lekounougou and Kocaefe (2012). According to published data, there are several reasons for the increase in the biological durability of thermally modified wood.…”
Section: Effect Of Thermal Modification Temperature On the Mechanicalsupporting
confidence: 64%
“…and Lekounougou and Kocaefe (2012). The presence of high MC observed in some samples can be considered due to the fungal degradation explained by the oxidative degradation of carbohydrates with the release of water molecules as indicated by Zabel and Morell (1992) and Borrega et al (2009).…”
Section: Effect Of Thermal Modification Temperature On the Mechanicalmentioning
confidence: 90%
See 1 more Smart Citation
“…Many VOCs are produced and released during wood heat treatments. These compounds are mainly derived from volatile extractives and evaporable byproducts formed from the degradation of wood components (Lekounougou and Kocaefe 2012;Candelier et al 2013b). The devolatilization analysis is of great importance to better understand the wood thermo degradation mechanisms as well as controlling hazardous substance emissions in VOCs.…”
Section: Kinetic Analysis For the Non-extracted And Extracted Eucalyptusmentioning
confidence: 99%
“…Three major components (cellulose, lignin and hemicelluloses) along with low molecular compounds are the major components of wood [1][2][3]. In order to understand wood degradation mechanisms taking place under natural environmental conditions (during material service life), many researchers have simulated accelerated ageing by using biodegradation factors, such as soft, brown and white rot fungi or termites [4][5][6]; thermal and hydro-thermal ageing [7][8][9] or weathering and UV light exposure [10,11].…”
Section: Introductionmentioning
confidence: 99%